Changes in determinants of compulsory community treatment over 11 years. A population-based analysis of linked mental health databases - Kisely, S.; Xiao, J.; Jian, Le (2015)
Differences in patient characteristics, legislation and service setting may explain variations in the reported efficacy of compulsory treatment orders (CTOs). Our objective was to investigate factors associated with CTO placement in Western Australia and see if there were any changes over the 11 years following their introduction. We used three linked Western Australian databases to compare 2958 patients on community treatment orders with an equal number of controls matched on age, sex and diagnosis, as well as 2832 consecutive controls selected on date of discharge from inpatient care or CTO placement. Multivariate analyses were used to further examine potential predictors of a CTO. The incidence of CTOs, and the characteristics of patients placed on these orders, showed little change over 11 years. They tended to be younger and male with schizophrenia or other non-affective psychotic disorders. Previous health service use as an inpatient or outpatient also predicted compulsory community treatment. Psychiatrists in Western Australia appear to be applying community treatment orders to similar types of patient as elsewhere, but unlike other jurisdictions, use has not increased. We need further research to establish the relative contribution of patient characteristics, legislation and service setting toward the use and outcome of CTOs.